2020
DOI: 10.1002/gps.5323
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric symptom profiles ofcommunity‐dwellingpersons living with dementia: Factor structures revisited

Abstract: Objectives: Most persons living with dementia (PLWD) will develop neuropsychiatric symptoms (NPS) at some point. NPS are often clustered into subsyndromes with other related symptoms, but the evidence supporting commonly used clusters is insufficient. We reexamine behavioral clusters in community-dwelling PLWD and identify associated risk factors and potential contributors. Methods: This study used baseline data from a longitudinal behavioral intervention study of 250 community-dwelling older adults with demen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…Anxiety is not only associated with poor quality of life in people with cognitive impairment, 50,51 but also it is associated with increased caregiver burden among family members. 50,52 In this study, we observed that increased social isolation was related to increased anxiety among people with cognitive impairment.…”
Section: Variance Inflation Factormentioning
confidence: 99%
“…Anxiety is not only associated with poor quality of life in people with cognitive impairment, 50,51 but also it is associated with increased caregiver burden among family members. 50,52 In this study, we observed that increased social isolation was related to increased anxiety among people with cognitive impairment.…”
Section: Variance Inflation Factormentioning
confidence: 99%
“…Numerous studies have grouped NPSs into subsyndromes [ 13 , 15 , 21 , 27 , 45 , 47 , 50 , 51 ]; however, few studies have examined their distribution based on GDS stage [ 52 ], especially in community-dwelling patients. This grouping by subsyndrome is of great interest from the clinical point of view, especially in a scenario of high frequency consultations, as happens in PC, because it allows simplification of the detection of NPSs and provides a more suitable approach with pharmacological or nonpharmacological measures based on the predominating symptom at any given time [ 53 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have grouped NPSs into subsyndromes (13,15,21,27,45,47,50,51); however, few studies have examined their distribution based on GDS stage (52), especially in community-dwelling patients. This grouping by subsyndrome is of great interest from the clinical point of view, especially in a scenario of high frequency consultations, as happens in PC, because it allows simpli cation of the detection of NPSs and provides a more suitable approach with pharmacological or nonpharmacological measures based on the predominating symptom at any given time (53)(54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%